Solutions for better tolerance and more effective application of eye drops - Eliza Wolska; Agata Kupiec (Polish Pharmaceutical Society, 2021)
When developing and manufacturing ophthalmic drugs, consideration should be given not only to product quality and treatment efficacy, but also to patient safety and convenience. Currently, two important directions of technological development in the field of eye drops preparations can be distinguished. These are new solutions that would enable the production of preservative-free preparations and the design of devices and packaging that would facilitate the correct application of eye drops by the patient. This publication focuses on an overview of interesting solutions in these two topics. Firstly, manufacturers of ophthalmic drugs are moving away from the use of preservatives in formulations, which is entirely justified due to the potential for irritation and toxicity. In such a situation, however, sterile dosing of the eye drops becomes a challenge when the bottle contains multiple doses. As a result, many innovations have emerged, such as specially designed multi-dose eye drop dispensers that protects the contents against microbial contamination, single-dose packaging intended to be used up immediately after opening, and finally reclosable one-day packaging. Eye drops dispensers should be economical, provide the longest possible shelf life of the solution without preservatives, and allow easy application with precise eye targeting and quantity dispensing. If they are recyclable, they will also benefit the environment. Secondly, self-instillation of eye drops is the most common method of drug delivery in the treatment of various ocular conditions, therefore a properly conducted procedure largely determines the effectiveness of treatment. In this respect, eye drop dispensing aids could be very useful tool to facilitate application. It has been shown that poor application of eye drops is very often associated with old age, poor vision and limited manual dexterity of patients. These patients in particular require a simplified treatment regimen and medical devices to support application. Therefore, the adaptation and evolution in the delivery and application of known and commonly used preparations in ophthalmic therapy are as important as innovations in this field. The proposed additional attachments and aids should be easy to assemble and use with the currently available packaging. It is expected that the proposed solutions in the field of packaging technology and application aids will significantly improve patient's comfort, safety and thereby patient compliance, which will result in increased therapeutic effectiveness.